PENGEMBANGAN BAHAN AJAR MODUL SEJARAH KEBUDAYAAN ISLAM BERBASIS PROBLEM SOLVING UNTUK MENINGKATKAN HASIL BELAJAR SISWA MADRASAH TSANAWIYAH - Sitti Aisyah; Misykat Malik Ibrahim; Wahyuni Ismail (Fakultas Agama Islam Universitas Wiralodra, 2022)
This study aims to analyze the need to develop problem solving-based Islamic Cultural History module teaching materials, and 2) analyze the level of validity of problem solving-based Islamic Cultural History module development teaching materials. This research includes development research (R&D) which produces Islamic Cultural History module teaching materials. problem solving based. Based on the results of the study that: (1) based on the results of the needs identification interview, several obstacles were found during the learning of Islamic Cultural History, (2) the results of the validation by the material expert team obtained an average of 3.67 with very feasible criteria and media experts obtained an average of 3, 76 with very feasible criteria, and the practicality of the product is in the very practical category with an average score of 84.0%.